2015
DOI: 10.1681/asn.2014080804
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells in Kidney Transplant Biopsy Samples Are Associated with T Cell Infiltration and Poor Allograft Survival

Abstract: Progress in long-term renal allograft survival continues to lag behind the progress in short-term transplant outcomes. Dendritic cells are the most efficient antigen-presenting cells, but surprisingly little attention has been paid to their presence in transplanted kidneys. We used dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin as a marker of dendritic cells in 105 allograft biopsy samples from 105 kidney transplant recipients. High dendritic cell density was associated with poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
6
32
0
Order By: Relevance
“…Cross‐talk between T cells and DCs in kidneys is well recognised in mouse models, and evidence from human kidney samples suggests that a similar inter‐relationship is involved in the initiation of immunological responses in the kidney. Biopsy tissues from renal allograft and patients with ANCA‐associated vasculitis both revealed a close proximity between CD3 + T cells and DC‐SIGN + DCs . We found that DC‐SIGN + DCs clustered with CD4 + or CD8 + T cells or ICAM‐3 + T cells in renal interstitium, and we also found that most CD4 + or CD8 + T cells expressed ICAM‐3.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Cross‐talk between T cells and DCs in kidneys is well recognised in mouse models, and evidence from human kidney samples suggests that a similar inter‐relationship is involved in the initiation of immunological responses in the kidney. Biopsy tissues from renal allograft and patients with ANCA‐associated vasculitis both revealed a close proximity between CD3 + T cells and DC‐SIGN + DCs . We found that DC‐SIGN + DCs clustered with CD4 + or CD8 + T cells or ICAM‐3 + T cells in renal interstitium, and we also found that most CD4 + or CD8 + T cells expressed ICAM‐3.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, the density of DC‐SIGN + cells was positively correlated with the density of CD4 + cells, CD8 + cells and ICAM‐3 + cells. These data suggest that renal DC‐SIGN + cells may induce kidney injury in IgAN by activating T cells …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Third, whether human monocytic cells show the same features of alloreactivity, including reliance on sensing donor SIRPα polymorphism, deserves careful investigation. In fact, DCs and macrophages are present in significant numbers in chronically rejected transplants in humans, and the degree to which they are present correlates with poor kidney allograft outcomes (22). …”
Section: Unanswered Questionsmentioning
confidence: 99%
“…The authors observed that DC-SIGN + cell density (3.8>hpf) was adversely associated with allograft function and survival (2-yr after biopsy, r=-0.36, p<0.001), and with increased proliferation of T cells (Ki67 + ) and higher inflammation scores (ti 2-3). Interestingly, DC-SIGN + cells clustered with lymphocytes were predominantly of recipient origin, especially at the later time points (8). This observation implies a possibly harmful effect of in situ DC-SIGN + DCs on the alloimmune response and provides a rationale for targeting DCs to halt allograft inflammation.…”
Section: Introductionmentioning
confidence: 99%